Immunological prophylaxis of the most common infectious diseases in children : methodical recommendations - Panko, N. O.; Rakovska, L. O.; Панько, Наталія Олександрівна; Раковська, Людмила Олександрівна (Kharkiv : V.N. Karazin Kharkiv National University, 2019)
Methodological recommendations provide information on the formation of children's immunity against the most common infectious diseases. Types of vaccines and indications for their use are described in details. A calendar of preventive vaccinations for children of different ages is provided. Methodical recommendations are worked out on the basis of the Program of discipline of «Pediatrics» for students of higher medical educational institutions of III–IV levels of accreditation, authorized by Ministry of Health of Ukraine. These recommendations are intended for the 6th year English-speaking medical students.

В методичних рекомендаціях надано інформацію щодо формування у дітей імунітету проти найбільш поширених інфекційних хвороб. Детально описуються типи вакцин та показання до їх застосування. Приводиться календар профілактичного щеплення для дітей різного віку. Методичні рекомендації розроблено на основі програми дисципліни «Педіатрія» для студентів вищих медичних навчальних закладів III–IV рівнів акредитації, затвердженої МОЗ України. Дані рекомендації призначені для студентів 6-го курсу медичного факультету англомовного навчання.
Імунопрофілактика найбільш поширених інфекційних захворювань у дітей : методичні рекомендації
Навчальне видання
Keywords: MEDICINE; SOCIAL SCIENCES; immunization; children; vaccine; schedule of vaccination; імунізація; діти; вакцина; календар вакцинації